1998
DOI: 10.1152/jappl.1998.84.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary disposition of lipophilic amine compounds in the isolated perfused rabbit lung

Abstract: We measured the pulmonary venous concentration vs. time curves for [3H]alfentanil, [14C]lidocaine, and [3H]codeine after the bolus injection of each of these lipophilic amine compounds (LAC) and a vascular-reference indicator (fluorescein isothiocyanate-dextran) into the pulmonary artery of isolated perfused rabbit lungs. A range of flows and perfusate albumin concentrations was studied. To evaluate the information content of the data, we developed a kinetic model describing the pulmonary disposition of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 33 publications
(97 reference statements)
2
64
0
Order By: Relevance
“…The phenylephrineinduced increase in RD p 2 by 41% and decrease of V p by 17% is comparable to the changes of 75 and 15%, respectively, reported after hypoxic pulmonary vasoconstriction (7). Because Audi et al (1) have shown that a flow change per se does not change RD p 2 , the increase in relative dispersion by phenylephrine may be attributed to an increased heterogeneity of flow distribution. Because of the small interstitial space of the lungs (v p ϳ0.02) (20), whole body methods are not sensitive enough to detect differences in the pulmonary distribution volumes and relative dispersion of indicators.…”
Section: Relative Dispersion In Pulmonary Circulationsupporting
confidence: 78%
See 1 more Smart Citation
“…The phenylephrineinduced increase in RD p 2 by 41% and decrease of V p by 17% is comparable to the changes of 75 and 15%, respectively, reported after hypoxic pulmonary vasoconstriction (7). Because Audi et al (1) have shown that a flow change per se does not change RD p 2 , the increase in relative dispersion by phenylephrine may be attributed to an increased heterogeneity of flow distribution. Because of the small interstitial space of the lungs (v p ϳ0.02) (20), whole body methods are not sensitive enough to detect differences in the pulmonary distribution volumes and relative dispersion of indicators.…”
Section: Relative Dispersion In Pulmonary Circulationsupporting
confidence: 78%
“…This holds especially for the relative dispersion in the systemic circulation in relation to whole body distribution of indicators. The relative dispersion of vascular markers has mostly been estimated by using isolated perfused organs, such as the lung (1,6,14), heart (4), and liver (29), whereas distributed models of blood-tissue exchange have been used for permeating indicators (3). In contrast to the wide use of both classical compartment models (8,10,18) and recirculatory compartmental models (11,15,16), only incomplete attempts have been made in the past to study whole body distribution of solutes on the basis of TTDs (25,30,33).…”
mentioning
confidence: 99%
“…Virtually all of the injected CoQ 1 H 2 was recovered as CoQ 1 H 2 in the venous effluent in normoxic and hyperoxic lungs at both flows. The observation that the CoQ 1 H 2 outflow curves at two different flows (10 and 30 ml/min) were virtually superimposable when the time axis for each curve was normalized to vascular mean transit time is a hallmark of a substance that freely permeates tissues (i.e., "flow limited")(2,3,6,8).…”
mentioning
confidence: 99%
“…The advection and diffusion of a nonmetabolizing substance is modeled by Eq. (2): (2) where C is the concentration of the substance, v is the advective velocity vector field describing the motion of blood in the vascular network, and D is the molecular diffusion coefficient in the tissue. Here diffusion is isotropic and occurs homogeneously throughout intravascular as well as extravascular regions.…”
Section: Modeling Advection and Diffusion In Three Dimensionsmentioning
confidence: 99%
“…For example, Audi et al 1,2 have noted that the Crone-Renkin model and other axially distributed descriptions of tracer transport may lead to variations in estimates of parameters (such as permeability) with flow. A comparison of the behavior of an alternative model (our three-dimensional network model) to that of axial-distributed models, provides new insight into this issue.…”
Section: Introductionmentioning
confidence: 99%